2012
DOI: 10.1111/j.1440-1754.2012.02555.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Parkinsonism

Abstract: We present the case of a 14-year-old boy presented with a recent history of progressive neurologic decline and extrapyramidal features. The history and findings with illustrative figures are detailed, and a diagnostic approach to the presentation is considered. The therapeutic options and broader management issues are briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Although the majority of PD cases appear to be sporadic, some specific genetic defects have been linked to familial PD, especially in patients with early onset juvenile parkinsonism. 1 Previous studies revealed that mutations in several genes such as parkin, PTENinduced putative kinase protein 1 (PINK1), Parkinsonism associated deglycase (DJ1), ATPase 13A2 (ATP13A2), phospholipase A2 group VI (PLA2G6), Fbox protein 7 (FBXO7), synaptojanin1 (SYNJ1), and DnaJ heat shock protein family (Hsp40) member C6 (DNAJC6) are associated with juvenile or early onset parkinsonism. [2][3][4][5] However, potential genetic causes still remain unidentified for some of the patient population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of PD cases appear to be sporadic, some specific genetic defects have been linked to familial PD, especially in patients with early onset juvenile parkinsonism. 1 Previous studies revealed that mutations in several genes such as parkin, PTENinduced putative kinase protein 1 (PINK1), Parkinsonism associated deglycase (DJ1), ATPase 13A2 (ATP13A2), phospholipase A2 group VI (PLA2G6), Fbox protein 7 (FBXO7), synaptojanin1 (SYNJ1), and DnaJ heat shock protein family (Hsp40) member C6 (DNAJC6) are associated with juvenile or early onset parkinsonism. [2][3][4][5] However, potential genetic causes still remain unidentified for some of the patient population.…”
mentioning
confidence: 99%
“…Multiple mechanisms may play a role in neurodegeneration in Parkinson's Disease (PD), including oxidative stress. [1][2][3] Given that dietary antioxidants (e.g., vitamins E, C, and carotenoids) can prevent oxidative damage, 4 it has been hypothesized that these nutrients could protect against PD. 5 However, previous epidemiological studies in this area have tended to be small and results have been inconsistent.…”
mentioning
confidence: 99%